Genome-Wide Identification and Expression Analysis of the Plant U-Box Protein Gene Family in Phyllostachys edulis - Zhou, Jie; Hu, Yaping; Li, Jiajia; Yu, Zhaoyan; Guo, Qirong (Frontiers in Genetics, 2021)
The U-box gene encodes a ubiquitin ligase that contains a U-box domain. The plant U-box (PUB) protein plays an important role in the plant stress response; however, very few studies have investigated the role of these proteins in Phyllostachys edulis. Thus, more research on PUB proteins is necessary to understand the mechanisms of stress tolerance in P. edulis. In this study, we identified 121 members of the PUB family in P. edulis (PePUB), using bioinformatics based on the P. edulis V2 genome build. The U-box genes of P. edulis showed an uneven distribution among the chromosomes. Phylogenetic analysis of the U-box genes between P. edulis and Arabidopsis thaliana suggested that these genes can be classified into eight subgroups (Groups I–VIII) based on their structural and phylogenetic features. All U-box genes and the structure of their encoded proteins were identified in P. edulis. We further investigated the expression pattern of PePUB genes in different tissues, including the leaves, panicles, rhizomes, roots, and shoots. The qRT-PCR results showed that expression of three genes, PePUB15, PePUB92, and PePUB120, was upregulated at low temperatures compared to that at 25°C. The expression levels of two PePUBs, PePUB60 and PePUB120, were upregulated under drought stress. These results suggest that the PePUB genes play an important role in resistance to low temperatures and drought in P. edulis. This research provides new insight into the function, diversity, and characterization of PUB genes in P. edulis and provides a basis for understanding their biological roles and molecular mechanisms.